2022
DOI: 10.1155/2022/3215461
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hydrostatic Pressure Promotes Cartilage Repair in an Inflammatory Environment through Hippo-YAP Signaling In Vitro and In Vivo

Abstract: The study of chondrogenic progenitor cells (CPCs) as seed cells has become a new focus of cartilage regeneration. The inflammatory environment of osteoarthritis (OA) inhibits the repair ability of CPCs. But the OA patients’ CPCs showed an excellent regeneration ability with intermittent hydrostatic pressure (IHP). However, the mechanism is unclear. We compared the expression of the Hippo signaling effect factor YAP between OA and normal cartilages. Then, the relationship between the Kellgren-Lawrence (K-L) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hydrostatic pressure (HP) is an important mechanical stimulus to which chondrocytes are exposed. Intermittent HP can boost the differentiation of CPCs to promote OA cartilage repair 167,168 . Ogura et al.…”
Section: Anti‐angiogenesis Strategies In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrostatic pressure (HP) is an important mechanical stimulus to which chondrocytes are exposed. Intermittent HP can boost the differentiation of CPCs to promote OA cartilage repair 167,168 . Ogura et al.…”
Section: Anti‐angiogenesis Strategies In Tissue Engineeringmentioning
confidence: 99%
“…Intermittent HP can boost the differentiation of CPCs to promote OA cartilage repair. 167,168 Ogura et al intermittently applied HP to collagen gel/sponge scaffolds containing human articular chondrocytes, resulting in increased ECM synthesis and accumulation. 169 In addition, Montagne et al used continuous high HP stimulation and observed that this condition was not conducive to maintaining the cell phenotype and matrix synthesis.…”
Section: In Vitro Bioreactors For Enhancing the Therapeutic Propertie...mentioning
confidence: 99%
“…Yao et al found a lower expression of YAP1 and higher expression of phosphorylated YAP1 in OA patients after balancing the age factors, and the inhibition degree of the YAP1 is positively correlated with the severity of OA. 144 Furthermore, appropriate mechanical stress could inhibit the Hippo signaling to up-regulate the expression of YAP1, which promotes chondrocyte proliferation and cartilage repair in OA. 144 According to a newly published study, both pharmacological inhibition and gene knockdown of YAP in OA chondrocytes reduce chondrocyte anabolic activity and cause further cartilage defect, while IGF-induced YAP nuclear translocation in turn promotes anabolic activity.…”
Section: Yap/taz and Oamentioning
confidence: 99%
“…144 Furthermore, appropriate mechanical stress could inhibit the Hippo signaling to up-regulate the expression of YAP1, which promotes chondrocyte proliferation and cartilage repair in OA. 144 According to a newly published study, both pharmacological inhibition and gene knockdown of YAP in OA chondrocytes reduce chondrocyte anabolic activity and cause further cartilage defect, while IGF-induced YAP nuclear translocation in turn promotes anabolic activity. 145 Consistent with that, several murine models of experimental OA revealed that YAP can facilitate chondrogenesis and cartilage reconstruction by the alternative Wnt…”
Section: Yap/taz and Oamentioning
confidence: 99%
See 1 more Smart Citation